Effect of Dual Endothelin Receptor Antagonist on a Retinal Degeneration Animal Model by Regulating Choroidal Microvascular Morphology - Xiaowei Zhu; Xuming Lin; Ying Xu; Naiyang Li; Qing Zhou; Xiaowei Sun; Yuanbin Li (Journal of Ophthalmology)
Objective. Clinical studies have found that increasing levels of plasma endothelin-1 (ET-1) might inhibit choroidal blood flow (BF) and promote choroidal vasoconstriction. This study was designed to investigate ET-1 levels and its effect on choroidal microvascular morphology in a retinitis pigmentosa (RP) animal model. Methods. Mice with retinal degeneration (rd10) were intragastrically administered bosentan, a dual endothelin receptor antagonist. We detected plasma ET-1 levels using an enzyme-linked immunosorbent assay (ELISA) kit at P14, P21, and P28 and evaluated ET-1 expression in RPE/choroid/sclera complexes using western blot and whole mount immunofluorescence staining at P28. Retinal thickness was measured using hematoxylin and eosin (H&E) staining at P28. At the same time, we also estimated choroidal microvascular densities using vascular luminal casting with a scanning electron microscope (SEM). Results. Plasma ET-1 levels were increased significantly in rd10 mice at P21 (65.48 ± 24.83 pg/ml) and P28 (85.89 ± 20.23 pg/ml) compared with C57BL/6J mice at P21 (33.52 ± 16.33 pg/ml) and P28 (42.38 ± 17.53 pg/ml); the expression of ET-1 was also upregulated in RPE/choroid/sclera complexes at P28. Bosentan inhibited ET-1 expression in plasma (P<0.05) and RPE/choroid/sclera complexes at P28 in rd10 mice. Choroidal microvascular densities were decreased in rd10 mice, and bosentan could weaken these changes. Conclusion. Plasma and local ET-1 was elevated in an animal model of RP, suggesting that it likely participates in the pathological progression of retinal degeneration and may thus provide a new intervention target. ET-1 blockade might exert its protective effect by elevating choroidal microvascular density via inhibition of ET-1.